В числителе: 6^-4 * 6^-4 в знаменателе: 6^-28 в числителе: 7^-7 * 7^-8 в знаменателе: 7^-28

В числителе: 6^-4 * 6^-4 в знаменателе: 6^-28 в числителе: 7^-7 * 7^-8 в знаменателе: 7^-28
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{6^{-4}6^{-4}}{6^{-28}} = \frac{6^{-4+(-4)}}{6^{-28}} =\frac{6^{-8}}{6^{-28}} =6^{-8-(-28)}} =6^{-8+28}} =6^{20}} \\ \\ \\ \frac{7^{-7}7^{-8}}{7^{-28}} = \frac{7^{-7+(-8)}}{7^{-28}} =\frac{7^{-7-8}}{7^{-28}} =\frac{7^{-15}}{7^{-28}} =7^{-15-(-28)}} =7^{-15+28}}=7^{13}}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы